2015
DOI: 10.1097/opx.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Early Resolved Acute Syphilitic Posterior Placoid Chorioretinitis

Abstract: In patients with ASPPC, fundus and OCT findings can spontaneously recover during the early clinical course before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
(4 reference statements)
1
12
0
Order By: Relevance
“…Similar to our report, it has been documented in immunocompetent patients. Franco et al and Ji et al reported findings of ASPPC in immunocompetent patients with spontaneous resolution without receiving any therapy 4 , 5 . On the other hand, our patient was initially treated with immunosuppressive therapy which is often not a suggested therapy for syphilis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Similar to our report, it has been documented in immunocompetent patients. Franco et al and Ji et al reported findings of ASPPC in immunocompetent patients with spontaneous resolution without receiving any therapy 4 , 5 . On the other hand, our patient was initially treated with immunosuppressive therapy which is often not a suggested therapy for syphilis.…”
Section: Discussionmentioning
confidence: 64%
“…ASPPC is a rare ocular manifestation of syphilis and its natural course is not well known 4, 5, 6 , 11 . It is characterized by the development of a placoid macular deposit in the outer retina 12 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, spontaneous resolution of ASPPC before initiation of systemic antimicrobial treatment has been reported in 5 cases [ 10 ], [ 11 ], [ 12 ], [ 13 ]. The first cases were described in 2015 by Ji et al [ 10 ], who reported two HIV-negative patients with ASPPC which spontaneously improved 10 days (for the first case) and 3 weeks (for the second case) after presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with ASPPC usually receive prompt antimicrobial treatment after serologic results, little is known about the natural course of the disease. To the best of our knowledge, only 5 cases of ASPPC with spontaneous improvement have been reported [ 10 ], [ 11 ], [ 12 ], [ 13 ]. We report the natural course and the multimodal retinal imaging features of an additional case, and discuss the pathogenetic implications and the importance of early recognition of this rare clinical entity.…”
Section: Introductionmentioning
confidence: 99%
“…Subretinal fluid accumulation can presented in cases of ASPPC[ 3 ] and spontaneously resolved fluid accumulation can occur within these patients even without treatment. [ 6 7 ] Unlike CSCR, in which the ellipsoid zone recovers when subretinal fluid accumulation is resolved,[ 8 ] patients with ASPPC presented with ellipsoid zone loss and scattered RPE nodules after spontaneous subretinal fluid resolution. [ 3 9 ] FA applied to our patient's eyes also revealed vitreous opacity and retinal phlebitis, which suggested the involvement of inflammation or infectious disease instead of CSCR.…”
Section: Discussionmentioning
confidence: 99%